Phenotypic and Genotypic Characterization of NPRL2-Related Epilepsy: Two Case Reports and Literature Review - Sun, Yulin; Wan, Lin; Yan, Huimin; Li, Zhichao; Yang, Guang (Frontiers in Neurology, 2021)
The phenotype of nitrogen permease regulator-like 2 (NPRL2) gene-related epilepsy clinically manifests as a range of epilepsy syndromes, including familial focal epilepsy with variable foci (FFEVF), sleep-related hypermotor epilepsy (SHE), temporal lobe epilepsy (TLE), frontal lobe epilepsy (FLE), and infantile spasms (IS). The association between phenotype and genotype of NPRL2 variants has not been widely explored. This study aimed to explore the phenotype and genotype spectrum of NPRL2-related epilepsy. Here, we presented two clinical cases with NPRL2-related epilepsy, and discussed the characteristics, diagnosis, and treatment processes in the context of existing literature. Two novel NPRL2 likely pathogenic variants were identified by next-generation sequencing, including one splicing mutation (c.933-1G>A), and one frameshift mutation (c.257delG). The results of literature review showed that there were a total of 20 patients with NPRL2-related epilepsy whose mutations were mostly missense and hereditary. These findings indicate that the possibility of NPRL2 gene mutations in focal epilepsy should be considered for patients with family history, and that patients carrying different NPRL2 variants have different clinical manifestations. Our study expanded the genotype spectrum of NPRL2 and suggested that the type of NPRL2 variants might provide important information for the prognosis evaluation.